Association Between Heart Transplantation and Subsequent Risk of Stroke Among Patients With Heart Failure. Issue 3 (March 2019) - Merkler, Alexander E.; Chen, Monica L.; Parikh, Neal S.; Murthy, Santosh B.; Yaghi, Shadi; Goyal, Parag; Okin, Peter M.; Karas, Maria G.; Navi, Babak B.; Iadecola, Costantino; Kamel, Hooman
Abstract : Background and Purpose—: It is uncertain whether heart transplantation decreases the risk of stroke. The objective of our study was to determine whether heart transplantation is associated with a decreased risk of subsequent stroke among patients with heart failure awaiting transplantation. Methods—: We performed a retrospective cohort study using administrative data from New York, California, and Florida between 2005 and 2015. Individuals with heart failure awaiting heart transplantation were identified using previously validated International Classification of Diseases, Ninth Revision, Clinical Modification diagnosis codes for heart failure in combination with code V49.83 for awaiting organ transplant status. Individuals with prior stroke were excluded. Our primary exposure variable was heart transplantation, modeled as a time-varying covariate and defined by procedure code 37.51. The primary outcome was stroke, defined as the composite of ischemic and hemorrhagic stroke. Survival statistics were used to calculate stroke incidence, and Cox proportional hazards analysis was used to determine the association between heart transplantation and stroke while adjusting for demographics, stroke risk factors, Elixhauser comorbidities, and implantation of a left ventricular assist device. Results—: We identified 7848 patients with heart failure awaiting heart transplantation, of whom 1068 (13.6%) underwent heart transplantation. During a mean follow-up of 2.7 years, we identified 428 strokes. The annual incidence of stroke was 0.7% (95% CI, 0.5%–1.0%) after heart transplantation versus 2.4% (95% CI, 2.2%–2.6%) among those awaiting heart transplantation. After adjustment for potential confounders, heart transplantation was associated with a lower risk of stroke (hazard ratio, 0.4; 95% CI, 0.2–0.6). Conclusions—: Heart transplantation is associated with a decreased risk of stroke among patients with heart failure awaiting transplantation.